Sleep and children with special needs - Limonšek, Ivanka (Nursing in the 21st Century, 2012)
SLEEP AND CHILDREN WITH SPECIAL NEEDS Mental retardation is not a disease. Children with special needs need guidance, occasional or full assistance or support, respectively. Their development is different as in healthy peers. Changes are evident in many areas, even in sleep. Sleep as a life activity in children with special needs has different approaches in providing necessary conditions for sleep. A case report of the institution ZUDV Dornava confirmed the fact, that sleep disturbances are more frequent in persons with special needs, because of all other factors which have influence on their development. External factors are together with the basic disorder increasing sleep difficulties. The treatment should be approached individually and holistically.